Marine Geohazards of the Bay of Naples (Southern Tyrrhenian Sea, Italy): A Review Integrating Morpho-Bathymetric and Seismo-Stratigraphic Analysis - Gemma Aiello; Mauro Caccavale (GeoHazards, 2024)
Marine geohazards in the Bay of Naples, an eruptive region during the late Quaternary, have been assessed based on both morpho-bathymetric and seismic data. Previously identified areas of high marine hazard with slide potential (northern Ischia slope, Naples canyons, and Sorrento Peninsula–Capri slope) have been confirmed and integrated through the seismo-stratigraphic analysis of selected seismic sections. We evaluated the occurrence of important fossil submarine landslides in the stratigraphic record. Several kinds of submarine landslides have been individuated through morpho-bathymetric and seismic interpretation, including creeping, debris avalanches, and debris flows, among others, often controlled by volcanic eruptions. Submarine landslides of Naples Bay are primary geohazards in the marine and coastal areas, which has been ascertained with significant volcanic and tsunami hazards involving the gulf. Despite previous studies on these topics, much work is still needed to compile a systematic database of the submarine landslides of the Bay of Naples, representing a future step of this research.